LAND TENURE DISPUTE RESOLUTION TANGERANG CITY GOVERNMENT AGAINST THE MINISTRY OF LAW AND HUMAN RIGHTS - Dedeh Latipah; Hayati Nufus; Upik Mutiara (Legal Standing : Jurnal Ilmu Hukum, 2020)
The sociological approach of law in explaining and understanding agrarian conflicts.Because the normative, legalistic, and positivistic legal systems that have been used arenot sufficient to explain and even provide solutions for agriculturaldisputes thatcontinue to drag on and become chronic. Agrarian conflict is not only a positive legalproblem but more substantially a complex problem, which is related to other socialissues such as law, economy, and culture. The sociological,standard approach is usedto understand agrarian conflict, especially in the conflict between the Tangerang CityGovernment and the Minister of Home Affairs in Land Management Rights in asociological and punitive way toBE understand agrarian conflicts more fully andtherefore can find ways to resolve and more judicial solutions for Public. The agrarianconflict between the Tangerang City Government and the Minister of Home Affairs inthe Right to Manage Land the competition started when the Minister of Justice andHuman Rights teased the Tangerang City Government. As a result, the Tangerang CityGovernment will not serve several services on the land of the Ministry of Law andHuman Rights (Kemkumham), especially offices until there is communication with theMinistry of Law and Human Rights. The sociology of law approach has relevance toexplain it. This approach is considered capable of explaining the socio-legal reality insociety, especially those related to agrarian conflicts.